Influencing factors of hospitalization in maintenance haemodialysis outpatients after a diagnosis of COVID-19 - Yanlin Zhu; Jie He; Yunming Li; Mingyuan Cao; Yue Cheng; Fan Zhang; Guchuan Yang (Annals of Medicine, 2023)
AbstractBackground The clinical manifestations of maintenance haemodialysis (MHD) outpatients diagnosed with coronavirus disease 2019 (COVID-19) are highly heterogeneous. They are prone to progress to severe conditions, and they often require hospitalization. To better guide the management of MHD outpatients, this retrospective observational study assessed risk factors for hospitalization of MHD patients after a diagnosis of COVID-19.Methods The demographic data, comorbidities, laboratory indicators and imaging data of 128 MHD outpatients at our haemodialysis centre with confirmed COVID-19 infection from December 2022 to January 2023 were collected. The relationships between these factors and hospitalization of patients were analyzed.Results Among the 128 patients, 25 (19.53%) were hospitalized. One of the 25 inpatients was mechanically ventilated, and two of them died. Multivariate logistic regression analysis showed that the hospitalization rate was correlated with age, comorbid diabetes and peripheral blood lymphocyte count.Conclusion Older age, comorbid diabetes and lower lymphocyte count are important risk factors for hospitalization of MHD outpatients after a diagnosis of COVID-19. Focusing on these factors may help in early identification of patients who may need to be admitted due to potential disease progression.